Mechanistic Insight to the Reaction Pathway of Aerobic Oxidative C–C Bond Cleavage of α-Hydroxy Ketones - Liu, Hui; Jiang, Xuefeng (Synlett, 2013)
A novel transition-metal-free aerobic oxidative C–C bond-cleavage method has been developed. Oxygen, the ideal oxidant, was used as the oxidizing reagent. The dimeric intermediate and 18O-isotopic-labeling control experiments partially disclosed the reaction mechanism.
Keywords: α-hydroxy ketones; esterification; aerobic oxidation; C–C bond cleavage; transition-metal-free